Pengaruh Ide Kreatif Dalam Mengembangkan Dakwah di Masjid Jami’ Nurul Ikhsan - Nurmia Shinta; Erwan Effendy,; Zulfikar Kelana Sipayung (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to develop students' insights in creating creative ideas for da'wah activities, so that the da'wah delivered is more interesting so that mad'u are not bored and understand the material presented more easily. A Da'i and Da'iyah must be able to create good creative ideas, namely by always paying attention to the people they face (the congregation), because preaching must be adapted to the conditions of their mad'u. Therefore preaching to children, youth and parents should ideally be different. This is considering that intelligence and the problems faced by the mad'u. The analytical method used in this research is descriptive qualitative analysis, in which the research process is more focused on interviews and direct field observations so that researchers better understand how the conditions related to the things studied are perfect. Basically, in preaching we will be more effective and not boring when we are going to convey da'wah materials. We must have creative ideas and think about how the da'wah delivered can be accepted and understood by the mad'u. Keywords: creating ideas, creative, preaching